Anti‐plasma cell treatment in refractory autoimmune hemolytic anemia in a child with multivisceral transplant. (6th June 2021) - Ghobrial, Shahira; Gonzalez, Corina Elena; Kaufman, Stuart; Yazigi, Nada; Matsumoto, Cal; Fishbein, Thomas; Hawksworth, Jason; Ekong, Udeme D.; Kroemer, Alexander; Khan, Khalid
Abstract: Background: Warm‐antibody AIHA is known to complicate solid organ (SOT) and HSCT, the disease maybe refractory to standard therapy. Immunosuppressive therapies as well as IVIG, and rituximab have been the main stay of treatment. Over the past decade, B‐lymphocyte targeted, anti‐CD‐20 antibody has been recognized in the treatment of autoimmune diseases and utilized in AIHA. Bortezomib, a proteasome inhibitor that causes apoptosis of plasma cells, is an appealing targeted therapy in secondary AIHA and has demonstrated efficacy in HSCT patients. From our experience, we advocate for early targeted therapy that combines B cell with plasma cell depletion. Case Report: We describe a 4‐year‐old‐girl with stage III neuroblastoma, complicated with intestinal necrosis needing multivisceral transplant developed warm AIHA 1‐year after transplantation, and following an adenovirus infection. She received immunoglobulin therapy, rituximab, sirolimus, plasmapheresis, and long‐term prednisolone with no sustained benefit while developing spinal fractures related to the latter therapy. She received bortezomib for intractable AIHA in combination with rituximab with no appreciable adverse effects. Three years later the child remains in remission with normal reticulocyte and recovered B cells. In the interim, she required chelation therapy for iron overload related to blood transfusion requirement during the treatment of AIHA. Conclusion: We propose early targeted anti‐plasma cell therapy with steroid burst, IVIG, rituximab, and possible plasmapheresis may reduce morbidity in secondary refractory w‐AIHA.